Strategy of Department of Industry and Cooperation of Pidie Jaya District in Developing Small and Medium Micro Enterprises - Zulfikar, Zulfikar; Suriadi, Mimin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The importance of UMKM for various parties makes it often the object of study and research which mostly discusses its development. This study deals with strategy of department of industry and cooperation of Pidie Jaya District in developing small and medium micro enterprises. This study use a descriptive qualitative. The results are there are two strategy of the Pidie Jaya trade industry and cooperatives service in developing small and medium enterprises:1) capital provision strategy; 2) Training / Empowerment Strategy. There are four efforts that improved micro, small and medium enterprises in Pidie Jaya Regency: 1) strength-opportunity strategy; 2) strength-threat strategy; 3) weakness-opportunity strategy; 4) weakness-threat strategy. It can be concluded that: (1).Capital strategy: assistance provided by the government is very supportive of community UKM, but in terms of capital / loans, UKM expect the government to allocate more budget considering that capital or raw materials and machines are so expensive. (1)The training strategy, the training strategy provided by the agency is very useful for the business community in Pidie Jaya district.